Pemahaman dan Pembentukan Karakter Masyarakat: Realitas dan Pandangan Antropologi - Effendi, Nursyirwan (TINGKAP, 2015)
This article raised issues related to anthropological views in the character building of the community. The authors look at the concept of scientific and socio-anthropological approach in building the character of the community as well as the approach of behaviorism, interactionism, and construction. In this paper the authors also described how the construction of the human characters in the study based on the anthropology and cross-cultural studies. Interestingly, this article attempts to discuss the dialectic model of role of science in building the character by using three approaches, namely behaviorism, interactionism, and construction, so as to provide answers about the position of science in the normative and academic levels in the character building.Keywords:Â  character, character building, anthropological perspective